Zielnik Stefana Falimirza a słownik Jana Mączyńskiego - Jankowiak, Lucyna Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The article partly confirms W. Kuraszkiewicz’s assumptions about Jan Mączyński adopting vocabulary (not only medical) from Stefan Falimirz’s herbarium (O ziołach i mocy ich). On the basis of 32 volumes of the Dictionary of Polish Language of the 16th Century, the author claims that 41 entries were included in Jan Mączyński’s dictionary, which definitely constitutes half of these influences.